2021
DOI: 10.1186/s12913-021-06226-5
|View full text |Cite
|
Sign up to set email alerts
|

Distance to primary care facilities and healthcare utilization for preschool children in rural northwestern Burkina Faso: results from a surveillance cohort

Abstract: Background Delays in care-seeking for childhood illness may lead to more severe outcomes. We evaluated whether community distance from a primary healthcare facility was associated with decreased healthcare utilization in a rural district of northwestern Burkina Faso. Methods We conducted passive surveillance of all government-run primary healthcare facilities in Nouna District, Burkina Faso from March 1 through May 31, 2020. All healthcare visits f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…37 Two possible explanations for this result include that there are no differences in care-seeking for underweight compared with normal weight children, or that increased distance from healthcare facilities does not influence healthcare utilization in the study area. 38 There was no evidence of seasonal differences in WAZ in this analysis. Burkina Faso, as in much of the Sahel, experiences seasonal food insecurity during the rainy season (approximately July through October), with an annual harvest typically in November.…”
Section: Discussionmentioning
confidence: 62%
“…37 Two possible explanations for this result include that there are no differences in care-seeking for underweight compared with normal weight children, or that increased distance from healthcare facilities does not influence healthcare utilization in the study area. 38 There was no evidence of seasonal differences in WAZ in this analysis. Burkina Faso, as in much of the Sahel, experiences seasonal food insecurity during the rainy season (approximately July through October), with an annual harvest typically in November.…”
Section: Discussionmentioning
confidence: 62%
“…In rural Burkina Faso, facility-diagnosed malaria cases have been shown to peak at 7 to 12 months of age. 21 The number of malaria deaths was small, and the CI included 1, and this finding may have been a result of chance.…”
Section: Discussionmentioning
confidence: 99%
“…These results support a study in rural northwestern Burkina Faso, where primary health care visit rates decreased with distance from the clinic. 46 A survey of global travel-time maps makes travel-time maps without access to health care. The study found that only 8.9 percent of the global population cannot reach a health service within an hour if they have access to a motorized vehicle.…”
Section: Discussionmentioning
confidence: 99%